Capital deaccumulation and the large persistent effects of financial crises - Matthew Knowles (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
In a panel of OECD and emerging economies, I find that recessions are associated with larger initial drops in investment and more persistent drops in output if they occur simultaneously with banking crises. Furthermore, the banking crises that are followed by more persistent output slumps are associated with particularly large initial drops in investment. I show that these patterns can arise in a model where a financial shock temporarily increases the costs of external finance for investing entrepreneurs. This leads to a drop in investment and a very persistent slump in output and employment, provided wages are sufficiently rigid. Critical to the model is the distinction between different types of capital with different depreciation rates. Intangible capital and equipment have high depreciation rates, leading these stocks to drop substantially when investment falls after a financial shock. I find that this mechanism can account for almost a third of the persistent drop in output and employment in the US Great Recession (2007-2014).
Keywords: E22; E32; E44; 330; Financial Shocks; Great Recession; Persistent Slumps; Intangible Capital